(untitled) (American Journal of Pedagogical and Educational Research, 2025)
Of all the arts, it is music that most directly influences human perception, because it has a strong influence on the subconscious level not only on a person’s feelings, but also on his mind. Music reflects a person’s moods and experiences, his emotional world. The subtlety, strength and diversity of mental states revealed in music constitute its main content.